Systematically Investigating the Qualities of Commercial Encapsulated and Industrial-Grade Bulk Fish Oils in the Chinese Market - Qian Zhou; Lili Xu; Yanan Xu; Qianqian Xue; Changhu Xue; Xiaoming Jiang; Yunqi Wen (Foods)
Fish oil is one of the most popular dietary nutritional supplements. Reports on the qualities of fish oils from Chinese markets are scarce, although the consumption of fish oil products in China is huge and increasing. This study systematically investigated the qualities of commercial encapsulated fish oils (CFs) and bulk fish oils (BFs) from Chinese markets, including oxidative level, sensory quality, color, metal element content, and unsaturated fatty acid content. Significant quality variations were observed both among individual CFs and between BFs: 65.2% of CFs (excluding one flavored sample) and one BF sample met China’s Grade II fish oil oxidation product standards; 80.8% of CFs and three BFs were within regulatory limits for heavy metal contamination. A distinct fishy odor was detected in four CFs and one BF sample, while a pronounced rancid odor was observed in one CF sample. The EPA contents in 64% of CFs and DHA contents in 48% of CFs met their labeled claims. Furthermore, these five quality parameter categories demonstrated non-significant intercorrelations, with the fish oil unit price being independent of quality. These findings indicated that most BFs require refinement, and CFs require implementation of low-temperature dark storage/transportation protocols. This study provided comprehensive quality benchmarks for fish oil production and marketing.